User Experience in Learning Management System: Edmodo versus Google Classroom - Hanifah Muslimah Az-zahra; Dini Nurhayati; Admaja Dwi Herlambang (Journal of Information Technology and Computer Science, 2022)
Nowadays, Learning Management System (LMS) is widely used to support the learning process. LMS becomes a medium of interaction between students and teachers. Poor usability and user experience (UX) of an LMS can make students spend more time learning the system than learning the educational content. Therefore, usability and user experience evaluation are important for e-learning. Edmodo and Google Classroom are two widely used LMS. This study involved students as inspectors to compare the user experience of Edmodo versus Google Classroom using Technique for User Experience Evaluation in E-learning (TUXEL). Inspectors divided into two groups: one group inspected Edmodo and another group inspected Google Classroom. After completing the inspection, the inspectors were asked to fill three questionnaires: usability inspection, general LMS / pedagogical usability inspection, and user experience. The data then processed and analyzed per category per dimension. The results of the overall general usability and pedagogical usability inspections show fewer problematic aspects in Edmodo (22 items) than Google Classroom (30 items). However, Google Classroom seems to be preferred by students because it is simpler, practical and, more comfortable. Edmodo is recommended for distance learning since it has more features. While Google Classroom is more suitable to be used as a support or complement for a learning course.